Perbandingan Kepadatan Kering Tanah Lempung Distabilisasi Serbuk Arang Tempurung Kelapa dengan Serbuk Arang Bambu - Yayuk Apriyanti; Ovin Sahara; Aisah Fitri; Ferra Fahriani (Universitas Islam 45, 2021)
Clay soil is the basic part of a building construction, but such type of soil has the stability problems, hence it needs to be stabilized to increase its bearing capacity. Some natural materials in Bangka Belitung Province have not been optimally utilized, e.g. coconut shells and bamboo, which can be used as stabilization materials. In this article, we compare the dry density of clay soil mixed with coconut shell charcoal powder to clay soil mixed with bamboo charcoal powder. The percentage of stabilizing material used is 5%, 10% and 15% of the dry soil weight. Soil classification is based on the Unified Soil Classification System (USCS) standard including the low plasticity inorganic clay (CL) group and following the standards of the American Association of State Highway and Transportation Officials Classification (AASHTO) including the A-6 soil group. The compaction test result show that the dry density of the clay soil increases with the addition of stabilization agent using either coconut shell charcoal powder or bamboo charcoal powder. The results were almost the same where the difference was only about 0.001 (gr / cm3) for the stabilizer mixture of 5% and 10% as well as the difference of 0.002% (gr / cm3) for the stabilizer mixture of 15%. The increase in soil dry density indicates that the bearing capacity of clay soil increases with the increase in the percentage of stabilizing material